INFLUENCE OF HISTORY OF INFECTIOUS DISEASES, LOW BIRTH WEIGHT, MATERNAL AGE AND SERVICES DURING PREGNANCY, ON THE INCIDENCE OF STUNTING IN TODDLERS - Medina, Audrey; Sabtian Sarwoko, Sabtian (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Stunting in toddlers is a serious health problem in Indonesia, with prevalence remaining high despite a decline in recent years. Factors such as history of infectious disease, low birth weight (LBW), maternal age at pregnancy, and health services during pregnancy are thought to contribute to the incidence of stunting. This study aimed to analyze the association between history of infectious diseases, LBW, maternal age during pregnancy, and health services during pregnancy with the incidence of stunting in toddlers in Kepur Village, Muara Enim Regency. This study used an observational analytic design with a cross-sectional approach. The sample consisted of 154 respondents randomly selected from the toddler population in Kepur Village. Data were collected through interviews using a questionnaire and analyzed using the Chi-Square test. The results showed a significant association between history of infectious disease (p=0.000), LBW (p=0.000), maternal age during pregnancy (p=0.000), and health services during pregnancy (p=0.000) with the incidence of stunting in toddlers. Factors such as history of infectious diseases, LBW, maternal age during pregnancy, and health services during pregnancy have a significant relationship with the incidence of stunting. Efforts are needed to prevent stunting through counseling on the prevention of infectious diseases, improving health services for pregnant women, and cross-sectoral cooperation to deal with nutrition and public health problems.